Aberrant abdominal umbilical arteries in VACTERL - Association: A first case report - Vichan Peonim (2018)
A 38-week-gestational age male neonatal death from a 27-year-old-mother was reported. The autopsy found multiple congenital anomalies such as scoliosis of thoracic spine with 13 pairs of ribs, anal atresia, bilateral renal agenesis, and club feet. These anomalies were diagnosed VACTERL - association that must include at least three out of six principal anomalies of previously mentioned, e.g., (1) V - vertebral defects, (2) A - anal atresia, (3) C - cardiac anomalies, (4) TE - tracheo-esophageal fistula, (5) R - renal anomalies, and (6) L - limb abnormalities. In addition, other anomalies were also observed in this case, i.e., cryptorchidism both sides, jejunal diverticulum, and aberrant abdominal umbilical arteries.